The Poetics and Politics of Cultural Studies in Aravind Adiga’s The White Tiger - Want, University of Kashmir, Srinagar, India, Lily (Asiatic: IIUM Journal of English Language and Literature, 2011)
Aravind Adiga’s The White Tiger (2008) can easily be placed in the gamut of Cultural Studies since it shares most of the features of this school. For example, it can easily be analysed as a form of cultural resistance to homogenising capitalism, as the emphasis throughout is on the particularities of the proletariat suppressed under the dominant high culture. But what strikes one as odd is that this particular class has been undermined in the text to such an extent that the writer not only fails to redefine the social order but also ends up as a spokesperson of the conventional Eurocentric perspective of the East to the extent that it has led literary critics to debate how far he fits a Western cosmopolitan model of writing. This paper, therefore, attempts to unravel these diametrically opposed strands in the fabric of The White Tiger as Adiga while silencing certain voices ends up allowing the narcissism of the Western culture raise its garrulous head.